The Effectiveness of Instagram Social Media as a Promotional Media at Bali Zoo Gianyar Tourist Attraction - Widyantara, I Made Sugi; Mertha, I Wayan; Widana, Ida Bagus Gede Agung (PT FORMOSA CENDEKIA GLOBAL, 2024)
Bali Zoo Gianyar tourist attraction is one of the tourist attractions that uses social media, especially Instagram as a promotional medium, therefore it is very important to know the effectiveness of social media in promoting a tourist attraction. The purpose of this study was to determine the effectiveness of Instagram social media as a promotional medium for Bali Zoo Gianyar tourist attraction. The respondents used were 100 domestic tourists with a quantitative approach with the AIDA analysis model. The results of this study show the Attention dimension (effectiveness = 75.6%); Interest dimension (effectiveness = 78.6%); Desire dimension (effectiveness = 68.5%); and Action dimension effectiveness = 68.1%). From the percentage results for each AIDA dimension, Instagram social media @BaliZoo is effective as a promotional medium for Bali Zoo Gianyar Tourist Attraction.